(De)motivation in the Preparatory Language Classroom: EFL Learners’ and Teachers’ Voices - Ayan, Hatice Çelebi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
This survey study aimed to explore EFL learners‟ (de)motivation in the preparatory classes at Eastern Mediterranean University (EMU). The survey involved 105 learners from the Pre-intermediate and Intermediate levels, as well as 30 English instructors of these learners. It adapted a questionnaire that was developed by Falout and Maruyama (2004) on the basis of the research to date and was reported to be a reliable tool (.87) The study addressed the following research questions: 1) To what extent are the preparatory EFL learners (de)motivated in their target language learning? 2) What are the language teachers‟ perceptions of their language learner‟s (de)motivational level? 3) Is there congruence between the respondents‟ „voices‟? The statistical analysis of the questionnaire data revealed the Cronbach‟s Alpha score of .88 for the Learners‟ Version, and .89 for the Teachers‟ Version of the Questionnaire. Further, the analysis of the EFL learners‟ responses showed overall an adequate level (M=3.74) of their motivation. These participants provided positive responses in relation to 36 items (averaging 3.50 or higher), and negative responses to 11 items (averaging below 3.5). However, the EFL teachers‟ perceptions of their learners‟ motivational level was overall lower (M=3.45) than that reported by the learners. The instructors expressed their favorable opinions in relation to 19 items, while less favorable opinions in relation to 28 items. Regarding the preparatory learners‟ reports across several factors, the analysis demonstrated their high motivational levels in relation to the Teacher (M=4.11), Attitude to the Target Community (M=3.99), Attitude to English (3.72); whereas adequate motivation in respect of Attitude of Group Members (M=3.58) and the Language Course (M=3.56), and lower motivation in relation to Self-confidence (M=3.15). As regards the language teachers‟ perceptions across the same factors, the analysis showed that they perceived their EFL learners as highly motivated in relation to the Teacher (M=4.12), Attitude to the Target Community (M=3.56), adequately motivated in respect of Attitude of Group Members (M=3.47); whereas less motivated in relation to Attitude to English (M=3.38), the Language Course (M=3.28), and Self-confidence (M=3.03). It should be noted that the overall average of the learners‟ reported motivational level in relation to the Teacher Factor was almost congruent with the overall average of the teachers‟ perceptions of their learners‟ motivational level in relation to the same factor. Further, the decreasing order of the overall averages of the learners‟ and teachers‟ responses was congruent in terms of the following factors: Attitude to the Target Community, the Language Course, and Self-confidence; whereas somewhat congruent in respect of such factors as Attitude to English and Attitude of Group Mmembers. However, except the Teacher Factor, the teachers perceived their learners as consistently less motivated across other factors as compared to the learner‟s related self-reports. Thus, the findings of the present survey seemed to indicate overall an adequate motivational level and a promising degree of congruence between the participants‟ voices in the preparatory EFL classrooms under investigation. However, the self- reported lower motivational level in relation to Self-confidence and perceived lack of motivation of the learners in respect of Attitude of Group Members, Attitude to English, the Language Course, as well as Self-confidence warranted attention. These results necessitate prompt pedagogical consideration and action on the part of the language school in order to improve the motivational level of the learners. This study can be considered significant in that it provided valuable insights into the motivational level in the preparatory English language classrooms. Keywords: (de)motivation, EFL preparatory learners, EFL teachers, factors

ÖZ : Bu anket çalışması Doğu Akdeniz Üniversitesi hazırlık sınıfındaki öğrencilerin motivasyonlarını veya varsa motivasyon bozukluklarını bulmayı amaçlamıştır. Bu çalışma ön-orta ve orta seviyede 105 öğrenciyi ve bu öğrencilerin 30 İngilizce eğitmenini kapsamaktadır. Çalışma, bugüne kadar araştırma temelinde Falout ve Maruyama (2004) tarafından geliştirilen ve güvenilir bir ölçek (.87) olduğu bildirilen bir anketi uyarlamıştır. Çalışma aşağıdaki araştırma sorularını ele almıştır: 1) Hedef dil öğrenmede İngilizce yabancı dil hazırlık öğrencileri ne ölçüde motivedir veya değildir? 2) Dil öğretmenlerinin dil öğrencilerinin motivasyon seviyeleri veya varsa motivasyon bozukluk seviyeleri ile ilgili algıları nelerdir? 3) Katılımcıların „görüşleri‟ arasında bir uyum var mıdır? Anket verilerinin istatistiksel analizi Cronbach Alpha puanı Öğrencilerin anket uyarlaması için .88, Öğretmenlerin anket uyarlaması için .89 olarak saptanmıştır. Ayrıca, İngilizce yabancı dil öğrencilerin cevaplarının analizi, onların motivasyonlarının genel olarak yeterli düzeyde (M=3.74) olduğunu göstermiştir. Bu katılımcılar 36 maddeye ilişkin olumlu (3.50 veya daha yüksek ortalama), ve 11 öğeye ilişkin olumsuz (3.5 veya aşağıda ortalama) yanıtlar vermiştir. Ancak, İngilizce yabancı dil öğretmenlerinin onların öğrencilerinin motivasyon seviyeleriyle ilgili algıları, öğrenciler tarafından bildirilenden genel olarak daha düşüktür (M=3.45). Eğitmenler 19 maddeye ilişkin olumlu görüşlerini, buna karşın 28 maddeye ilişkin olarak az olumlu görüşlerini ifade etmişlerdir. Hazırlık öğrencilerinin çeşitli faktörler karşısındaki raporlarına ilişkin, analiz onların öğretmenlerine (M=4.11), hedef topluluğa olan tutumlarına (M=3.99), İngilizceye olan tutumlarına (M=3.72) göre yüksek motivasyon seviyelerini, diğer bir taraftan gurup üyelerinin tutumlarına (M=3.58) göre yeterli motivasyon seviyelerini ve dil kursu (M=3.56), ve öz- güven (M=3.15) ile ilgili olarak daha düşük motivasyon seviyelerini göstermiştir. Aynı faktörler karşısında dil öğretmenlerinin algıları ile ilgili olarak, analiz onların İngilizce yabancı dil öğrencilerinin; öğretmenleri (M=4.12), hedef topluluğa olan tutumları (M=3.56) açısından son derece motive olduklarını, gurup üyelerine olan tutumları açısından yeterli bir şekilde motive olduklarını (M=3.47), diğer bir taraftan, İngilizceye olan tutumları (M=3.38), dil kursu (M=3.28), ve öz-güvenlerine (M=3.03) ilişkin daha az motive olduklarını algıladıklarını göstermiştir. Öğrencilerin öğretmen faktörüne ilişkin rapor edilmiş motivasyon seviyelerinin genel ortalaması, aynı faktör ile ilgili olarak öğretmenlerin onların öğrencilerinin motivasyon düzeyi ile ilgili algılarının genel ortalaması ile hemen hemen uyumlu olması dikkate alınmalıdır. Ayrıca, öğrenci ve öğretmenlerin yanıtlarının genel ortalamalarının azalan sırası aşağıdaki faktörler açısından uyumludur: hedef topluma olan tutum, dil kursu ve özgüven; diğer bir taraftan, İngilizceye olan tutum ve grup üyelerinin tutumu gibi faktörler bakımından biraz uyumludur. Ancak, öğretmen faktörü dışında, öğretmenler öğrencilerinin ilgili öz raporlarına göre diğer faktörler genelinde olduğu gibi sürekli daha az motive olduklarını algılamışlardır. Böylece, mevcut araştırmanın bulguları, yeterli bir motivasyon seviyesini ve soruşturma kapsamında hazırlık İngilizce yabancı dil sınıflarındaki katılımcıların ifadeleri arasındaki uyumun umut veren derecesini gösterir gibiydi. Ancak, öz-güvene ilişkin öz-bildirilen düşük motivasyon seviyesi ve öğrencilerin gurup üyelerinin tutumu, İngilizceye olan tutumu, dil kursuna olan tutumu, ve öz-güvene ilişkin algılanmış motivasyon bozukluğuna dikkat edilmelidir. Bu sonuçlar öğrencilerin motivasyon düzeylerini artırmak amacıyla acilen dil okulu bölümünde eğitsel önem ve eylem gerektirir. Bu çalışma, hazırlık İngilizce dil sınıflarındaki motivasyon seviyesine değerli bilgiler sağladığı için önemli kabul edilebilir. Anahtar kelimeler: (de) motivasyon, İngilizce yabancı dil hazırlık öğrencileri, İngilizce yabancı dil öğretmenleri, faktörler
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2014. Supervisor: Assoc. Prof. Dr. Gülşen Musayeva Vefalı.
Keywords: English Language Teaching (ELT); English Language - Study and Teaching; (de)motivation; EFL preparatory learners; EFL teachers; factors